E-system for education company - Khoh, Huey Hun (2011)
E-System for Education Company (EEC) is an online based management system for the purpose of making management much more systematic,secure and efficient.There are three main users which are staff,admin and customer which are parents by Tan Educations.The system has total six modules which are login and registration,lessons module,staff management, student management,courses and classes management and billing management.The problem statement of this system which is the current system which are only filing system that able to record the students,payment,records by handwriting and there is no well documented data in the current system for managing student and staff information and the records are incomplete.The objectives of this system are to develop a computerized and systematic online education based company,and to store the kindergarten information in database for effective management of the data.Existing systems in the market that is similar with E-System for Education Company, programming languages and tools used are compared.Rapid Application Development (RAD) has been implemented to develop this system.There are four phases which are requirements planning,user design, construction and cutover.